SAT0043 Ankylosing spondylitis and cardiac diseases. (1st June 2001) - Santos, FM; Alves, A; Catarino, C; Bento, L; Cotrim, C; Carrageta, M; Silva, JC
Abstract : Background: Ankylosing Spondylitis (AS) and other spondyloarthropathies (SPA), are associated with certain cardiologic problems. Objectives: To identify coexisting AS and SPA in selected cardiac patients (pts) and to investigate the cardiac status of pts with an established diagnosis of AS. Methods: An observational study involving two pt. groups was undertaken: Group 1 were young and middle-aged patients (<50 years at time of diagnosis), followed in the cardiology department for aortic valve disease and/or with a permanent pacemaker implanted. All pts were interviewed and examined. A pelvic X-ray and blood analysis for HLA B27 was performed. Group 2 were pts with an established diagnosis of AS and no clinical evidence of cardiovascular disease. A full history, clinical examination, 24-h Holter and doppler echocardiography were performed. Cardiac abnormalities were related to clinical features of AS. Results: Group 1: 14 pts with either an aortic valve replacement (AVR), aortic valve pathology and/or a permanent pacemaker were studied. 12 men and 2 women, with a mean age of 40 years (range 22–53) were observed. 9 pts had an AVR, 2 had aortic valva (AV) stenosis and 5 had a permanent pacemaker implamted. 2 of the pts had both an AVR and a permanent pacemaker. 1 of these pts was definitely diagnosed with AS and 2 pts were diagnosed as undifferentiated SPA. Group 2: 9 men and 8 women, with an average age of 43 years (min 23 and max 61) were included. Disease duration varied from 1 to 20 years with a mean of 8. Four (24%) pts had echocardiographic evidence of aortic valve thickening and regurgitation. Two pts also had left atrial dilatation. Holter exams were performed in 15 of the 17 pts. No significant conduction abnormalities or arrhythmias were apparent. The 4 pts with echocardiographic changes were older (>50 years in 3 cases) or had a high Basmi index. Conclusion: Young pts with AV disease or conduction disorders should be screened for AS. Regular cardiac monitoring of AS pts may help prevent the long term cardiac complications associated with this condition.